Analisis Penerapan Just In Time untuk Meningkatkan Tingkat Produktivitas - Ranti Dwi Berlianti Bachtiar; Epi Fitriah (UNISBA Press, 2022)
Abstract. The level of productivity is one of the important variables that affect the competition in the manufacturing industry. This is because the level of productivity is used as a means of controlling economic activity in a company. One of the benefits of implementing just in time is to increase the level of productivity. If the implementation of just in time is very good, the level of productivity will also increase. In fact, not all levels of productivity in a company can be increased by implementing just in time. The purposes of this research are: (1) To determine the implementation of just in time at CV Harmony, (2) To determine the level of productivity at CV Harmony, (3) To find out the analysis of the implementation of just in time can increase the level of productivity at CV Harmony. The research method used in this research is descriptive analysis method with a quantitative approach. Researchers used primary data obtained from thirteen respondents to the questionnaires distributed, as well as interviews with one of the managers at CV Harmony. Researchers also used secondary data from documentation to obtain data, namely the quantity of production units and labor hours at CV Harmony . The results of this study indicate that the implementation of just in time at CV Harmony is very good and the productivity level fluctuates, so it can be said that the implementation of just in time can increase the level of productivity at CV Harmony. Abstrak. Tingkat produktivitas adalah salah satu variabel penting yang mempengaruhi persaingan industri manufaktur. Hal tersebut disebabkan oleh tingkat produktivitas yang dijadikan sebagai alat pengendali aktivitas perekonomian di suatu perusahaan. Salah satu manfaat dari penerapan just in time adalah untuk meningkatkan tingkat produktivitas. Jika penerapan just in time sudah sangat baik, maka tingkat produktivitas juga akan meningkat. Pada kenyataannya, tidak semua tingkat produktivitas di suatu perusahaan dapat meningkat dengan penerapan just in time.juan dilakukannya penelitian ini adalah: (1) Untuk mengetahui penerapan just in time pada CV Harmony, (2) Untuk mengetahui tingkat produktivitas pada CV Harmony, (3) Untuk mengetahuil analisis penerapan just in time dapat meningkatkan tingkat produktivitas pada CV Harmony. Metode penelitian yang digunakan dalam penelitian ini adalah deskiptif analisis dengan pendekatan kuantitatif. Peneliti menggunakan data primer yang diperoleh dari tiga belas responden atas kuesioner yang disebarkan, serta wawancara dengan salah satu manajer di CV Harmony. Peneliti juga menggunakan data sekunder dari dokumentasi untuk memperoleh data yaitu kuantitas unit produksi dan jam tenaga kerja di CV Harmony . Hasil penelitian ini menunjukkan bahwa penerapan just in time di CV Harmony sangat baik dan tingkat produktivitas berfluktuatif, sehingga dapat dikatakan bahwa penerapan just in time dapat meningkatkan tingkat produktivitas pada CV Harmony.